Economic confidence, negative interest rates, and liquidity: Towards Keynesianism 2.0 - Ulrich van Suntum (Westfälische Wilhelms-Universität Münster, Centrum für Angewandte Wirtschaftsforschung (CAWM), 2009)
A model is developed which explains deep recessions like the recent crisis by a lack of economic confidence, going along with a high liquidity preference of both private households and the private banking system. Thus the paper argues for a new form of Keynesian policy, which rests on monetary rather than fiscal policy. In this approach, instead of borrowing in order to create a substitute demand, the state creates additional credit in order to restore private investment. While this might imply temporarily negative central bank interest rates, it does not require direct interventions in the private capital market by either the central bank or the government. It is argued that such an approach is both cheaper and more effective than the traditional deficit spending policy is.
Keywords: 330